Primary cutaneous B-cell lymphoma and chronic leg ulcers in a patient with type 2 diabetes. (24th May 2017) - Mantovani, Alessandro; Perrone, Fabrizia; Stoico, Vincenzo; Pichiri, Isabella; Salvotelli, Laura; Teobaldi, Ilaria; Bruti, Massimiliano; Conti, Michela; Cima, Luca; Eccher, Albino; Bonora, Enzo
Summary: The incidences of type 2 diabetes mellitus and many cancers are rapidly increasing worldwide. Diabetes is a strong risk factor for some cancers (including lymphomas) and is also associated with adverse cancer outcomes. After gastrointestinal tract, the skin is the second most frequent extranodal site involved by non-Hodgkin lymphomas and the cutaneous B-cell lymphomas (CBCLs) range from 25% to 30% of all primary cutaneous lymphomas. The primary cutaneous diffuse large B-cell lymphoma (PCDLBCL) is an aggressive lymphoma with a poor prognosis, representing roughly 20% of all primary CBCLs. Classically, the cutaneous manifestation of this lymphoma is a red or violaceous tumors arising on a leg. To date, despite the large body of evidence suggesting that diabetes is strongly associated with an increased risk of some cancers, very little information is available regarding a possible association between type 2 diabetes and primary cutaneous diffuse large B-cell lymphoma. In this report, we will present the case of a white adult patient with type 2 diabetes with chronic leg ulcers complicated by a primary cutaneous diffuse large B-cell lymphoma. Learning points: Diabetes mellitus is increasing worldwide as well as the incidence of many cancers. Diabetes mellitus is a powerful risk factor for some cancers (including lymphomas) and is strongly associated with adverse cancer outcomes. Seen that diabetes is strongly associated with an increased risk of cancers (including cutaneous lymphomas), clinicians should always keep in mind this complication in elderly patients with type 2 diabetes, even in a chronic leg ulcer with hypertrophy of the wound edge, which is hard to heal and does not have the typical characteristics of a diabetic or vascular ulcer. In these cases, a biopsy should be performed to rule out a neoplasm. Early diagnosis and correct management of cancer in a patient with type 2 diabetes are crucial to improve clinical outcomes.